2004
DOI: 10.3354/meps271267
|View full text |Cite
|
Sign up to set email alerts
|

Ocean-estuary coupling in the Oregon upwelling region: abundance and transport of juvenile fish and of crab megalopae

Abstract: Numerous species of fish and invertebrates move between the continental shelf and estuaries during their early life-history. The physical mechanisms that regulate such movement and the extent of coupling between the near-shore ocean and estuaries are poorly understood. It is unclear how, or whether, similar physical mechanisms regulate transport to the outer coast and between the outer coast and estuarine areas. We used high frequency light trap collections at 2 sites, outer coastal and estuarine, to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 44 publications
6
68
0
2
Order By: Relevance
“…current relaxation or westward currents, colonisation apparently varies as a function of tide. Our hypothesis is consistent with a 2-step model of larval supply formulated for coastal marine species in general (see Miller & Shanks 2004 for discussion) and supported by Carcinus maenas data from Portugal (Queiroga et al 2006). In addition, the influence of local movements of megalopae on colonisation patterns may be contingent on the overall number of larvae reaching the benthic habitats.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…current relaxation or westward currents, colonisation apparently varies as a function of tide. Our hypothesis is consistent with a 2-step model of larval supply formulated for coastal marine species in general (see Miller & Shanks 2004 for discussion) and supported by Carcinus maenas data from Portugal (Queiroga et al 2006). In addition, the influence of local movements of megalopae on colonisation patterns may be contingent on the overall number of larvae reaching the benthic habitats.…”
Section: Discussionsupporting
confidence: 73%
“…In the estuaries along the Portuguese coasts, zero time lags suggest STST, although the influence of internal waves cannot be disregarded (Queiroga et al 2006). Following Miller & Shanks (2004) and Queiroga et al (2006), the time lags of 1 to 5 d for Helgoland suggest a combined effect of STST and internal waves on larval colonisation. The STST has been invoked for megalopae invading estuaries: here cues associated with estuarine water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Crosscorrelograms indicated a delay of 0 d between tidal range and supply of C. maenas megalopae in the present study. This is similar to the studies of Moser & Macintosh (2001) and Paula et al (2001), but differs from the delays detected by Miller & Shanks (2004). Miller & Shanks (2004) found that maximum abundance of C. magister megalopae occurred 4 to 5 d after maximum amplitude of the tide, and they attributed this effect to a combination of onshore transport by internal waves and diel vertical migration on a background of tidal currents.…”
Section: Tide-driven Supplysupporting
confidence: 69%
“…For example, recruitment of Cancer magister to light traps was positively correlated with upwelling events and tidal forcing in Oregon (Miller & Shanks 2004). However, in Washington, C. magister recruitment to light traps was not significantly correlated with wind events or tidal forcing (Roegner et al 2003).…”
Section: Interspecific Differences In Settlement Timingmentioning
confidence: 99%
“…The relative importance of larval transport mechanisms can vary among years (Wing et al 2003) and regions (Johnson et al 1986, McConnaughey et al 1992, Roegner et al 2003, Miller & Shanks 2004. For example, recruitment of Cancer magister to light traps was positively correlated with upwelling events and tidal forcing in Oregon (Miller & Shanks 2004).…”
Section: Interspecific Differences In Settlement Timingmentioning
confidence: 99%